El mini golf y su incidencia en los turistas de la ruta del rio ciudad Quevedo, año 2021 - Calderon Ordoñez, Gerardo Daniel (2022)
Tourism is a factor that has been gaining strength over the last decades and has generated a favorable impact for the sector, both economically and socially. If we refer to Ecuador, we can say that it is a biodiverse country because it has numerous species of flora and fauna and also has beautiful landscapes and tourist attractions. The city of Quevedo is a cantonal capital that is located on the Ecuadorian coast of the province of Los Rios. It is divided into urban and rural parishes including the parish of San Cristobal where the Avenida Ruta del Rio is located.The following research project exposes the result of the work done, in order to respond to the problem detected, which is the mini golf and its impact on tourists of the Ruta del Rio Ciudad Quevedo, year 2022. The information was obtained according to the research techniques applied, since all the factors that affect and favor the subject of the study were analyzed, which allows the practical development of the study.In addition, it can be seen how Canton Quevedo has changed in recent years through this work, which is why this work is very helpful for the realization of the proposal presented.